Kurikulum 2013 dan Manajemen Mutu Terpadu dalam Pendidikan - Sakdun (AN NUR: Jurnal Studi Islam, 2013)
Curriculum of 2013, which applied to start the school year 2013/2014 still pose pros and cons among educational practitioners. Parties that supports the state that the curriculum compacting lesson so not 2013 burdening students, more focus on the challenges of the future of the nation, and not burden the teachers in the preparation of the curriculum unit level education. The curriculum was designed to improve the standard of four expected to become a benchmark of competence improvement graduate later. The standard is the standard of competence of graduates, contents, process standards and assessments. To realize this total quality in education, the implementation of pillars of TQM in curriculum development in 2013 will need serious attention and concern. There are five pillars at least of TQM, a focus on customer engagement, measurement, total commitment and sustained improvement. Curriculum developed by 2013 through the pillars of TQM, a student is expected to become the objects of education will have the ability and quality of excellence in creating quality total education in Indonesia to confront the global challenges in the future.